2018
DOI: 10.7224/1537-2073.2017-029
|View full text |Cite
|
Sign up to set email alerts
|

Short Report: Prevalence of Cognitive Impairment in Newly Diagnosed Relapsing-Remitting Multiple Sclerosis

Abstract: Background:Cognitive impairment is common in multiple sclerosis (MS) and can manifest early in the disease process, sometimes as early as the first demyelinating event. However, the frequency of cognitive impairment in a newly diagnosed MS population has not been evaluated comprehensively in a clinical population. We sought to examine the prevalence of cognitive impairment in relapsing-remitting MS (RRMS) within a year of diagnosis in a clinic where cognitive testing at diagnosis is part of routine practice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
27
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 35 publications
(29 citation statements)
references
References 26 publications
1
27
0
1
Order By: Relevance
“…Almost thirty years ago, in a population-based study performed by S. Rao et al, a 45% frequency of cognitive impairment in MS was found [12]. Other epidemiological studies reported frequencies of cognitive impairment in patients with MS between 40–70% in North America and Europe [19]. Frequencies of 40–60% have been reported in Latin America [20].…”
Section: Cognitive Impairment In Multiple Sclerosismentioning
confidence: 99%
“…Almost thirty years ago, in a population-based study performed by S. Rao et al, a 45% frequency of cognitive impairment in MS was found [12]. Other epidemiological studies reported frequencies of cognitive impairment in patients with MS between 40–70% in North America and Europe [19]. Frequencies of 40–60% have been reported in Latin America [20].…”
Section: Cognitive Impairment In Multiple Sclerosismentioning
confidence: 99%
“…MS is an immune-mediated disease that causes CNS damage in the form of demyelination and neurodegeneration. In addition to physical disability, learning and memory impairments occur in approximately half of all patients with MS. 1,2 The exact cause of MS is unknown, but dysregulated glutamate signaling and aberrant T-cell activation are consistently implicated as contributors to both physical and cognitive disease pathogenesis. 36 A number of trials have been conducted to identify either a disease-modifying therapy or a novel pharmacotherapy to treat MS-related cognitive impairment.…”
mentioning
confidence: 99%
“…Approximately 40-65% of people living with multiple sclerosis (MS) have difficulties with cognition [1][2][3]. With an average onset age of 30 years [4] and an unpredictable course (e.g.…”
Section: Introductionmentioning
confidence: 99%